Nepal : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
The ratio of projects at risk is 44 percent, which is much higher than a 20 percent Bank-wide average. The main problems seem to be an insufficient capacity to undertake procurement efficiently and an outdated system of procurement rules, many of which do not provide for transparent and competitive public purchasing of goods, works, and consultants' services. The report recommends the following: 1) Enact a modern, transparent, and competitive public procurement law, based on the UNCITRAL Model Law for Procurement, to apply to public procurement by all public entities in Nepal at all levels, as well as to parastatals. 2) create a small, independent procurement agency, with functions defined by the Public Procurement Law. 3) Pending the enactment of such a law, amend the Financial Administration (Related) Rules (FAR '99) to change the anti-competitive rules and practices listed in this report's Executive Summary. 4) Review and develop as needed standard bidding documents. 5) Develop and accelerate procurement training at all government levels. 6) Instruct the Auditor General's staff to assist on applying the donor's procurement rules and not local procurement rules. 7) Amend the anti-corruption legislation to impose harsh penalties and encourage reporting acts of corruption.